Two Sacred Bread Seals from Yalova/ Çobankale Excavation - Gülgün Köroğlu; Selçuk Seçkin (Art-Sanat)
Xerigordos (Çobankale), located in the Yalakdere Valley in the Altınova district of Yalova, is a particularly important castle settlement established on the main roads. The name of the castle is frequently mentioned in historical sources between the 11th and 14th centuries. During the archaeological excavations started in the castle with the permission of the Republic of Turkiye Ministry of Culture and Tourism, two terracotta seals with depictions of crosses on them were unearthed in the immediate surroundings of the architectural remains identified as a chapel. The fact that the seals were found around the chapel suggests that they were used for bread, which was believed to have been specially prepared and sealed before being baked and transformed into the body of Christ, to be distributed during the most important religious ceremony of Christianity, the consecration of bread and wine (Eucharist). The impressed surface of the conicalshaped sacramental bread seals is engraved with a gradually framed depiction of a cross. Other artifacts found during the excavations and comparisons with similar seals make it possible to date the bread seals to the Middle Byzantine period (11th-12th centuries). Within the scope of this study, the sacred bread seals unearthed in Çobankale excavations will be introduced, the polytheistic and monotheistic symbolic meaning of bread will be emphasized, and similar examples from the same period found in archaeological excavations will be discussed.